Unraveling Genetic Variation and Inheritance Patterns in Newly Developed Maize Hybrids for Improving Late Wilt Disease Resistance and Agronomic Performance Under Artificial Inoculation Conditions - Nasr A. Ghazy; Mayasar I. Al-Zaban; Fatmah Ahmed Safhi; Maha Aljabri; Doaa A. Kafsheer; Imen Ben Abdelmalek; Mohamed M. Kamara; Elsayed Mansour; Salem Hamden (Life)
Late wilt disease caused by the fungal pathogen Magnaporthiopsis maydis represents a major threat to maize cultivation in the Mediterranean region. Developing resistant hybrids and high-yielding offers a cost-effective and environmentally sustainable solution to mitigate yield losses. Therefore, this study evaluated genetic variation, combining abilities, and inheritance patterns in newly developed twenty-seven maize hybrids for grain yield and resistance to late wilt disease under artificial inoculation across two growing seasons. The results indicated highly significant variations among assessed hybrids for all measured traits. Combining ability analysis identified IL-306, IL-304, and IL-303 as excellent combiners for grain yield and late wilt resistance, positioning them as superior candidates for hybrid development. Additionally, IL-302 was identified as a strong general combiner for earliness, and IL-307 and IL-309 demonstrated potential for producing short-statured hybrids critical for improving lodging tolerance and maximizing yield. Specific combining ability effects indicated promising earliness, yield, and disease-resistance hybrids, including IL-303×T2 and IL-306×T1. GGE biplots presented optimal line×tester combinations, offering strategic guidance for hybrid development. The principal component analysis demonstrated strong associations between grain yield, late wilt resistance, and key agronomic traits, such as ear length and kernel number. The observed robust positive association between grain yield, late wilt resistance, and yield attributes suggests selection potential for improving maize productivity. Moreover, the genotypic correlations revealed that earlier silking, taller plants, and higher kernel counts were strongly linked to enhanced yield potential. Genetic parameter estimates indicated a predominance of non-additive genetic effects for most traits, with moderate to high broad-sense heritability suggesting substantial genetic contributions to phenotypic variance. This research provides valuable insights to support the development of disease-resistant and high-yielding maize hybrids addressing critical food security challenges.